Análisis de eficiencia e integración energética del esterilizador de la planta piloto de la Universidad Icesi. (2021)
Icesi university counts with a three-stage double tube sterilization equipment designed to guarantee innocuous condition required on biochemical engineering bioprocesses. Since its operations started, the equipment has not been exposed to an efficiency and energetic analysis, which suggests the possibility to improve the equipment this way. As a solution for this problematic, alternatives are going to be suggested based on the characterization of the equipment and statistical analysis of the critical variables identified in the sterilization process to improve its energetic efficiency. Therefore, the current project is focused on propose and validate at least one energetic efficiency alternative for the Icesi university pilot plant employing a methodology consisting on the energetic efficiency model research, the choice for a work fluid and a design of experiment (DOE) to evaluate the technical-economic viability of the alternatives proposed.